34‐1: Novel Liquid Crystal Display Mode SUVA4&SUVA5 with Double Photo Alignment Technology for High Definition Display. Issue 1 (28th June 2022) - Li, Fan; Wang, Zhi-gang; Peng, Lin; Zhang, Yong; Han, Hai-bin; Zhou, Peng; Kambe, Makoto
Abstract : In order to achieve the high transmittance of the high‐definition Display/8K Display panel, the B19 factory has successfully developed a new photo alignment process‐double photo alignment technology SUVA4 and SUV AS, which is the world's first. This new technology reduces the dark lines generated by the pixel ideal alignment division patterns, thereby achieving high panel transmittance. At the same time, the SUVA4 uses the VATN method, which can achieve high panel contrast.